Complications of bone transport technique using the Ilizarov method in the lower extremity: a retrospective analysis of 282 consecutive cases over 10 years - Yanshi Liu; Maimaiaili Yushan; Zhenhui Liu; Jialin Liu; Chuang Ma; Aihemaitijiang Yusufu (BMC Musculoskeletal Disorders, 2020)
Abstract Background The treatment of large bone defects in lower limbs is a serious challenge for orthopedic surgeons and patients. The bone transport technique using the Ilizarov method has become the main treatment option for the reconstruction of bone defect. However, inevitable difficulties and complications related to bone transport technique have been reported by many studies. The purpose of this study was to evaluate the effectiveness and complications of bone transport technique using Ilizarov method in the treatment of bone defect of lower extremity. Methods The study was conducted on 282 patients who underwent bone transport procedures using Ilizarov method at our institution from January 2007 to June 2017. Patient’s demographic data, complications and clinical outcomes at minimum of 2 years follow-up were collected and retrospectively analyzed. All difficulties that related to bone transport were documented according to Paley’s classification. The clinical outcomes were evaluated using Association for the Study and Application of the Method of Ilizarov criteria (ASAMI) at last clinical visit. Results There were 243 male and 39 females with a mean age of 40 years (range 18–65 years). The mean defect was 6.56 ± 2.15 cm, whereas single level transport in 221 cases and double level transport in 61 cases. There were 189 problems, 166 obstacles and 406 complications (257 minor and 149 major complications), and the average complication rate per patients consists of 0.91 minor and 0.53 major complications. The top five complications were pin-site infection (65.96%), axial deviation (40.78%), joint stiffness (23.76%), soft tissue incarceration (22.34%) and delayed union of the docking site (13.48%).The ASAMI bony result was excellent in 233 patients, good in 32, fair in 5 and poor in 12. The ASAMI functional result was excellent in 136 patients, good in 88, fair in 47, poor in 11. Conclusion Bone transport is a reliable method for reconstruction of bone defects in the femur and tibia. Awareness of predictable complications is beneficial to prevent or early detection of the expected complication which can improve the risk-benefit balance.